Global burden of endometriosis from 1990 to 2021 and projections to 2050: a comprehensive analysis based on the global burden of disease study 2021 - Yu, Xiaochuan; Shi, Lijuan; Deng, Xiaopeng; Zhang, Yating; Wang, Huali (Frontiers in Global Women's Health, 2025)
ObjectiveEndometriosis (EMT) is a prevalent gynecological disorder characterized by chronic pain, menstrual irregularities, and infertility. This study aims to evaluate the global burden of EMT from 1990 to 2021 and to project trends up to 2050.MethodsData from the Global Burden of Disease (GBD) 2021 database were utilized to analyze mortality, incidence, prevalence, and disability-adjusted life years (DALYs). Trends were assessed using age-standardized rates (ASR) and estimated annual percentage change (EAPC). Future burdens were projected using ARIMA and exponential smoothing models.ResultsIn 2021, there were 3,447,126 new cases of EMT reported globally. The age-standardized incidence rate (ASIR) experienced a decline of 1.07% from 1990 to 2021, while the age-standardized prevalence rate (ASPR) decreased by 0.95%. The incidence of EMT peaked among women aged 20–24 years, whereas mortality rates increased with advancing age. Projections suggest that by 2050, EMT-related deaths will rise to 68 cases, and the number of disability-adjusted life years (DALYs) will increase to 2,260,948, despite ongoing declines in both ASIR and ASPR.ConclusionAlthough the incidence and prevalence rates of EMT are declining, the disease burden remains significant among women of reproductive age. The anticipated rise in mortality and disability-adjusted life years (DALYs) in the future underscores the necessity for targeted public health policies. This study provides evidence to inform global prevention strategies. Future research should investigate the effects of population aging and lifestyle changes on the burden of EMT.